Ondansetron Treatment in a Child Presenting with Chronic Intractable Pruritus - Chantal Frigon; Joëlle Desparmet (Pain Research and Management)
The case of a seven-year-old boy with chronic pruritus secondary to a giant congenital melanocytic nevus is presented. The pruritus did not respond to conventional antipruritic drug treatment, but responded to ondansetron, a selective antagonist of 5-hydroxytryptamine type 3 receptors.